ANALISIS PENGARUH DUKUNGAN ORANG TUA, PERAN GURU, DAN LINGKUNGAN BELAJAR PADA PRESTASI SISWA - Qanitatin, Millati; Anis Sabila, Rara; Hanif, Ma'mun (CV. Kalimasada Group, 2025)
This study aims to analyze the influence of parental support, teacher roles, and learning environments on students’ academic achievement. To achieve this objective, the study employs a library research method by collecting, reviewing, and comparing various scholarly sources such as journals, books, and previous research relevant to the variables under study. The analysis is conducted using content analysis techniques to identify relationships, dominant findings, and patterns of interaction among the factors that affect academic performance. The results of the literature review indicate that parental support, teacher roles, and learning environments contribute significantly and complement one another in improving students’ academic achievement. Parental support influences learning outcomes through the provision of motivation, attention, and learning facilities; teacher roles determine instructional effectiveness through pedagogical and professional competencies; and a conducive learning environment enhances students’ focus, comfort, and engagement in learning activities. These three factors interact directly within Bronfenbrenner’s ecological theory, particularly within the microsystem that shapes students’ academic development. Therefore, this study concludes that academic achievement is not solely determined by individual abilities but also by the optimal collaboration between families, teachers, and learning environments.